PENGARUH KINERJA GURU EKONOMI TERHADAP PEMAHAMAN SISWA MENGENAI KONSEP LAPORAN KEUANGAN - Alisa Hariyatii; Witarsa Witarsa; Achmadi Achmadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis thesis entitled "the effect of the performance analysis of Teacher Skills Create financial reports In SMK Independent Vampires". The research in this thesis aimed to know how the performance of economics teacher against a student's Understanding of the concept of financial reports In a standalone CMS Pontianak.Research methods used in this research was quantitative. The results of this research were: 1) the performance of economics teacher in SMK Independent Vampires showed a positive performance with performance levels 73.53%.2) Understanding financial statements about the concept of students in SMK Standalone Pontianak average understanding of students and 63.4 of 65.76.Means of understanding the students experienced an increase of 2.36% of the concept of financial statements.3) there was the influence of performance analysis of teacher skills students create financial reports in a standalone CMS Pontianak, count of r Results of 0.48 indicates that the free variables (X) with varibel bound (Y) or Influences the performance of economics teacher Towards the understanding of the Students to the concept of financial reports in a standalone CMS Pontianak was positively and significantly with the category of being.4) how big the influence of performance analysis of teacher skills students create financial reports in a standalone CMS Pontianak.Keyword : Financial Reporting Skills, The Performance Of Teachers Of Economics